Handle decompositions of simply connected five-manifolds. I - Shkol’nikov, Yu. A. (Ukrains’kyi Matematychnyi Zhurnal, 1993)
Handle decompositions of simply connected smooth or piecewise linear five-manifolds are considered. The basic concepts and constructions necessary for proving our main result are introduced.